OPTIMIZING FOOD SECURITY IN YEMEN: UN WFP EFFORTS TOWARD ZERO HUNGER (2022–2024) - Diana Theresia Klau; Januari Pratama Nurratri Trisnaningtyas (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study analyzes the implementation of the United Nations World Food Programme (WFP) in Yemen in supporting the achievement of Sustainable Development Goal (SDG) 2 on eradicating hunger and improving food security during 2022–2024. The study focuses on evaluating the effectiveness of six key WFP programs, namely the General Food Assistance (GFA), Cash Assistance Programme, Nutrition Programme, School Feeding Programme, Livelihoods and Resilience Programme, and Enabling Services & Humanitarian Logistics, in addressing the severe food crisis caused by prolonged conflict, political instability, and economic decline. Using a qualitative descriptive method based on literature review and analysis of official WFP and UN reports, the research examines how these programs contributed to improving food access, reducing acute malnutrition, and strengthening community resilience. The findings show that WFP’s interventions successfully prevented mass starvation and supported the national food system, yet challenges remain due to limited funding, logistical constraints, and high dependency on external assistance. Strengthened cooperation between WFP, the Yemeni government, and international partners is essential to ensure sustainable progress toward achieving SDG 2: Zero Hunger.